The Tetracentron genome provides insight into the early evolution of eudicots and the formation of vessel elements - Liu, Ping-Li; Zhang, Xi; Mao, Jian-Feng; Hong, Yan-Ming; Zhang, Ren-Gang; E, Yilan; Nie, Shuai; Jia, Kaihua; Jiang, Chen-Kun; He, Jian; Shen, Weiwei; He, Qizouhong; et al. (Genome biology, 2020)
BACKGROUND: Tetracentron sinense is an endemic and endangered deciduous tree. It belongs to the Trochodendrales, one of four early diverging lineages of eudicots known for having vesselless secondary wood. Sequencing and resequencing of the T. sinense genome will help us understand eudicot evolution, the genetic basis of tracheary element development, and the genetic diversity of this relict species. RESULTS: Here, we report a chromosome-scale assembly of the T. sinense genome. We assemble the 1.07 Gb genome sequence into 24 chromosomes and annotate 32,690 protein-coding genes. Phylogenomic analyses verify that the Trochodendrales and core eudicots are sister lineages and showed that two whole-genome duplications occurred in the Trochodendrales approximately 82 and 59 million years ago. Synteny analyses suggest that the γ event, resulting in paleohexaploidy, may have only happened in core eudicots. Interestingly, we find that vessel elements are present in T. sinense, which has two orthologs of AtVND7, the master regulator of vessel formation. T. sinense also has several key genes regulated by or regulating TsVND7.2 and their regulatory relationship resembles that in Arabidopsis thaliana. Resequencing and population genomics reveals high levels of genetic diversity of T. sinense and identifies four refugia in China. CONCLUSIONS: The T. sinense genome provides a unique reference for inferring the early evolution of eudicots and the mechanisms underlying vessel element formation. Population genomics analysis of T. sinense reveals its genetic diversity and geographic structure with implications for conservation.
Keywords: Base Sequence; Resequencing; Genetic diversity; Sequence Analysis; Xylem; transkripční faktory; China; Genome, Plant; VND7; Plant Proteins; genom; Transcription Factors; sekvenční analýza; Genome; Evolution, Molecular; molekulární evoluce; rostlinné proteiny; Genetic Variation; Phylogenomic; Phylogeny; Whole genome duplication; xylém; sekvence nukleotidů; Čína; Arabidopsis; Tetracentron sinense; syntenie; Magnoliopsida; fylogeneze; genetická variace; Synteny; genom rostlinný; Vessel